If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2)(2)(-1)=x
We move all terms to the left:
(2)(2)(-1)-(x)=0
We add all the numbers together, and all the variables
-1x-22=0
We move all terms containing x to the left, all other terms to the right
-x=22
x=22/-1
x=-22
| h/9=3=2 | | c/6+8=10 | | 2x+15+3x=12x-20 | | 3+3(x-4)-10=-45 | | 6w-14=34 | | 1068=6(x+19) | | 16+3+5p-3p=3+4p | | -3x=2(x+3) | | |k+1|=1 | | 4x-2(x-4)=-6+5x+8 | | 4+1+8a+8a=4a-5+7a | | n-18=19 | | 7+2n=7n-8 | | x/9+13=0 | | -7(k+9)=9(k+-5)+-14k | | 8-4(f-3)=0 | | -7(k+9)=9(k+-5)-14k | | 5+7x+x=1+7x+1 | | 14n=-126 | | -7(x+6)-3(3x-3)=-65 | | 9k-16=52 | | g+143=1000 | | 33/4=r=1/8 | | №23x=10 | | 4z-3(z-6)=3=2z | | -4m-8=54 | | 2-2m=-20 | | 14-x=4+2x | | 21=-7×n | | 28j=952 | | 95x-15=-12 | | -27d=270 |